Spiritus loci : a theological method for contemporary church architecture - Daelemans, Bert. (Studies in Religion and the Arts, 2015)
In Spiritus Loci Bert Daelemans, who graduated as an architect and a theologian, provides an interdisciplinary method for the theological assessment of church architecture. Rather than a theory, this method is based on case studies of contemporary buildings (1995-2015), which are often criticized for lacking theological depth. In a threefold method, the author brings to light the ways in which architecture can be theology - or theotopy - by focusing on topoi (places) rather than logoi (words). Churches reveal our relationship with God by engaging our body, mind, and community. This method proves relevant not only for the way we perceive these buildings, but also for the way we use them, especially in our prophetic engagement for a better world.